Dedusting ash briquette binder, dedusting ash briquette and preparation method of dedusting ash briquette
By using dust removal ash briquette adhesive with completely inorganic components, the problem of dust removal ash briquette is solved, the mechanical properties are improved, secondary dust pollution is reduced, and more efficient resource utilization and environmental protection effects are achieved.
Patent Information
- Application Number
- CN202411909795.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, dust removal ash briquette is prone to shattering, causing secondary dust pollution and zinc ash to enter the dust removal system again during the rebate process, affecting resource utilization efficiency and environmental protection effect.
Dust removal ash briquetting adhesive with all-inorganic components, including MgO, MgCl2, CaO and montmorillonite, is used to prepare dust removal ash briquetting with good mechanical properties through specific mass ratios and treatment methods.
It improves the mechanical properties of dust removal ash briquettes, reduces the risk of crushing, reduces secondary dust pollution, enhances resource utilization efficiency, and is of environmental significance.
Smart Images

Figure CN119707432A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cold pressed block manufacturing, and in particular to a dust ash pressed block binder, a dust ash pressed block and a preparation method thereof. Background Art
[0002] Innovating the comprehensive utilization model of bulk solid waste, promoting "no solid waste leaving the factory" in the iron and steel metallurgical industry, and strengthening the full utilization of dust ash solid waste resources are difficult problems that iron and steel metallurgical enterprises must solve. Scientific research and a large number of practical applications have confirmed that steel slag can be used for the production of sound-absorbing materials and cement; the main components of desulfurization products can be widely used in construction and medical materials; dust with high iron and zinc content can be used to prepare foam metals, slag-making agents, or returned to the blast furnace as ironmaking raw materials. The TFe content of converter dust fine ash is more than 50%, and usually contains a certain amount of CaO, and the TFe content of iron oxide scale is more than 60%.
[0003] The main components of converter dust are Fe, Ca, Mg and other elements, and about 15kg of dust is produced for every ton of steel produced. The specific surface area of these dusts can reach 4.2m 2 / g, the particle size is fine, usually with an average particle size in the range of 20μm to 50μm, which makes it easy to reduce the air permeability of the material layer when it is returned as iron-making raw material, reduce production energy efficiency and increase the risk of accidents.
[0004] The dust produced by the iron-making yard and steel-rolling process contains a large amount of iron oxide scale. In normal steel enterprises, the amount of iron oxide scale produced usually accounts for 1% to 2% of the total steel production. Iron oxide scale is usually used for recycle ironmaking, steelmaking, and powder metallurgy processes. However, in addition to powder metallurgy, which is more difficult to handle, iron oxide scale has the same problem as converter dust, and the particle size is too small, which is not conducive to the smelting process.
[0005] In the past, many steel companies returned the dust (or iron-containing dust) to the sintering process as ingredients, but the Zn, K, Na and other components contained in the dust brought many problems to the sintering process, such as alkali metal enrichment, resulting in reduced output and quality of sintered ore. Therefore, briquetting the dust not only saves storage space and is less likely to cause secondary lift pollution, but also makes it more conducive for the iron-containing dust to adapt to various working conditions, increase its utilization efficiency, and reduce the difficulty of resource recovery. It has important environmental significance.
[0006] At present, most of the iron-containing dust is directly returned to the sintering process. Although it can recover some iron elements, it has a certain impact on the quality of the sintered ore and increases the content of zinc in the finished product, which is not conducive to the subsequent ironmaking process. In response to the above problems, a treatment method of adding iron-containing dust to the converter as a slag-making agent has emerged in recent years. During the exploration, people found that this method can greatly reduce the storage cost of dust. Compared with the method of returning the material to sintering, this briquetting method of recovering iron elements avoids a lot of original problems, and can also be effectively utilized in processes other than the converter.
[0007] However, the current briquetting process often has the problem of easy breakage of briquettes, which will lead to secondary dust pollution and the zinc-containing ash will re-enter the dust removal system during the return process. Summary of the invention
[0008] In order to solve the above problems in the prior art, the purpose of the present invention is to provide a dust ash briquetting binder, a dust ash briquetting and a preparation method thereof. The present invention provides a binder with all inorganic components, which is applied in the dust ash briquetting process, and the obtained finished product has good mechanical properties.
[0009] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, a dust ash briquetting binder is provided, which comprises, by mass, 0.8 to 1.2 parts of agent A, 1.5 to 2.1 parts of agent B, and 2.1 to 2.9 parts of a molding agent; wherein the agent A comprises MgO and MgCl2; the agent B comprises CaO and a buffer; and the molding agent comprises montmorillonite.
[0010] The present invention selects a binder of all-inorganic components, which will not generate carbon deposits when used in preparing dust ash compacts, thereby improving the overall performance of the compacts.
[0011] In addition, the inorganic substances in the dust ash briquetting binder of the present invention are mostly alkaline and have a suitable pH. Therefore, the binder has a wide range of applications and is suitable for dust ash generated in various processes in the production process of the steel industry, including but not limited to sintering head and tail ash, pellet ash, ore trough dust ash, iron-making yard dust ash, blast furnace slag dust ash, oxygen blowing furnace and electric furnace dust ash (steelmaking ash), refining furnace dust ash, iron-mixing furnace dust ash, coking ash, and steel rolling oxide scale.
[0012] In some preferred embodiments of the present invention, the mass ratio of MgO to MgCl2 is (1.5-2.5): (0.7-1.3).
[0013] In some preferred embodiments of the present invention, the mass ratio of CaO to buffer is (1.5-2.5):(4-6).
[0014] In some preferred embodiments of the present invention, the montmorillonite is calcium-based montmorillonite, with a particle size satisfying 90% passing through an 800-mesh sieve, a pH value ≥ 6.5, and a blue absorption amount ≥ 42 g / 100 g.
[0015] In some preferred embodiments of the present invention, the buffer comprises one or a combination of two or more of KH2PO4, acetic acid, and potassium acetate.
[0016] In some preferred embodiments of the present invention, the MgO is calcined;
[0017] Preferably, the calcination temperature is 1050-1350°C and the time is 3-6h;
[0018] Preferably, the MgCl2 is dried;
[0019] Preferably, the particle size of the agent A satisfies that 90% of the particle size passes through an 800-mesh sieve. The above particle size is preferred to facilitate more uniform mixing.
[0020] In some preferred embodiments of the present invention, the molding agent is dried at 105° C. for 3 to 6 hours before use.
[0021] According to the above preferred calcination treatment temperature and calcination time range, it is more conducive to the strength of the briquette. If it exceeds this range, it is easy to cause insufficient strength and easy to break during storage and transportation.
[0022] In some preferred embodiments of the present invention, the ash is mixed with the above-mentioned ash briquetting binder in a mass ratio of (75-92): (8-25) and then pressed to obtain the briquetting product.
[0023] In some preferred embodiments of the present invention, the dust removal ash includes one or a combination of two or more of steelmaking coarse ash, steelmaking fine ash, steelmaking sludge, and iron oxide scale.
[0024] In some preferred embodiments of the present invention, the dust removal ash is composed of the steelmaking coarse ash, the steelmaking fine ash, the steelmaking sludge, and the oxidized iron scale in a mass ratio of (10-30): (30-60): (5-15): (15-35). The cold pressed block obtained by pressing the dust removal ash according to the preferred ratio has better mechanical strength.
[0025] In some preferred embodiments of the present invention, the particle size of the dust removal ash satisfies that 90% passes through an 800-mesh sieve. The above particle size is preferred to facilitate more uniform mixing.
[0026] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned dust ash briquette, which comprises:
[0027] S1, mixing the agent A, the agent B, the molding agent, and water in a mass ratio of (0.8-1.2):(1.5-2.1):(2.1-2.9):(2.2-4.5), and stirring at 45-75° C. to obtain the dust ash briquetting binder;
[0028] S2, mixing the dust removal ash and the dust removal ash briquetting binder, and performing a mixing process to obtain a slurry;
[0029] S3, pressing the sludge, the pressing pressure is 5-15 MPa, and the pressing time is 15-30 minutes.
[0030] In some preferred embodiments of the present invention, within 1 hour before the pressing process, S1 further comprises:
[0031] The agent A is mixed with water at a mass ratio of 1:0.95-1.20 to obtain an A premix; the agent B is mixed with water at a mass ratio of 1:1.05-1.35 to obtain a B premix; the A premix and the B premix are stirred at 45-75° C. to obtain an A mixed solution and a B mixed solution respectively;
[0032] Secondly, the A mixed solution, the B mixed solution, the molding agent and the water are mixed according to the ratio.
[0033] By premixing in the above preferred manner, Agent A and Agent B can be mixed and gelled quickly, thereby promoting uniform mixing and agglomeration with the dust removal ash material.
[0034] Compared with the prior art, the beneficial effects of the present invention include at least:
[0035] 1. The present invention has a wide range of applications and can be applied to dust removal ash in various steel industries, including but not limited to sintering machine head, machine tail ash, pellet ash, ore trough dust removal ash, iron-making field dust removal ash, blast furnace slag dust removal ash, oxygen blowing furnace and electric furnace dust removal ash (steelmaking ash), refining furnace dust removal ash, iron mixing furnace dust removal ash, coking ash, and steel rolling scale;
[0036] 2. The binder of the present invention is all inorganic, has a low price, and can avoid the impact of carbon deposition and other problems during the calcination process on the recycling process. The inorganic substances introduced in the present invention are mostly alkaline, which is harmless to the sintering process and the converter slag making process;
[0037] 3. The finished briquette of the present invention has good mechanical properties and is not easy to break when placed or collided at room temperature or high temperature, and has a lower probability of secondary lift pollution and material blockage. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1The test results of the drop strength test in Example 2 are shown.
[0039] Figure 2 The test results of the drop strength test in Example 3 are shown.
[0040] Figure 3 The test results of the drop strength test in Example 4 are shown. DETAILED DESCRIPTION
[0041] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0042] Example 1
[0043] This embodiment uses a small laboratory device to prepare briquette, which specifically includes:
[0044] Take 56g of ash from the front and lower part of the evaporative cooler after the converter of a steel plant, 12g of converter primary dust removal ash (steelmaking coarse ash), 153g of converter primary, secondary and tertiary dust removal ash (steelmaking fine ash), 34g of wet dust removal sludge (steelmaking sludge), and 85g of rolled iron oxide scale, and mix them in a mixer for 30 minutes; set the oven temperature at 105°C and the relative humidity not exceeding 50%, and put the mixed materials into the oven for drying for 12 hours. Then put the dried materials into a planetary ball mill and grind them until the materials pass through an 800-mesh sieve and the material mass loss does not exceed 5%. Store the mixed materials in a container, mark them as dust removal ash, and place them in a cool and dry place for later use.
[0045] Take 4.56g of industrial-grade MgO and calcine it at 1200℃ for 5h. Take 2.28g of industrial-grade MgCl2 and dry it in an oven at 110℃ and relative humidity not exceeding 50% for 4.5h. Pass the two magnesium-based materials through an 800-mesh sieve with a mass loss of no more than 5%. Seal them with plastic film, mark them as Agent A, and place them in a cool and dry place for later use.
[0046] Take 3.52g of industrial-grade CaO and 8.76g of KH2PO4, mix them, seal them with plastic film, mark them as agent B, and place them in a cool and dry place for later use.
[0047] The laboratory montmorillonite sample was tested, and its blue absorption was 42.36g / 100g, and the pH value was 7.1 (0.2g of montmorillonite sample was placed in 20ml of distilled water, heated in a water bath and cooled, and the method was from the montmorillonite quality standard WS1-X343-Z2004-2011), which met the requirements; 40.92g of calcium-based montmorillonite was taken, sieved through an 800-mesh sieve, and the sieved montmorillonite was dried in an oven at 105°C, RH≤50%, poured into a beaker, sealed with plastic film, marked as a molding agent, and placed in a cool and dry place for use.
[0048] Take out Agent A and Agent B, add 7.2g of deionized water to Agent A, and add 14.72g of deionized water to Agent B, respectively, and stir them in a 60℃ water bath. After 15 minutes, stop stirring, immediately mix the mixture in the two beakers with the molding agent, add 22.4g of deionized water, and continue to stir in a 60℃ water bath for 10 minutes. Put the evenly stirred materials into the container marked with dust removal briquetting binder.
[0049] Put the dust removal ash and dust removal ash briquetting binder into the mixer for mixing. After 30 minutes, take out the mud-like product. Place a 50×50×50 (mm) mold at the predetermined position of the briquetting machine, fill the mold with excessive mud material, and briquette until the pressure index on the briquetting machine is 8MPa. Maintain for 15 minutes, release the pressure of the briquetting machine, remove the mold, clean up the excess material around the mold, put it in a 105℃ oven, take it out after 3 hours, carefully demould the material briquetting and the mold, and observe that there is no obvious damage on the surface of the briquetting.
[0050] The shatter strength was tested according to the YB / T 4606-2017 specification, and the result was 92.1%. The compressive strength was tested and the result was 2088N.
[0051] Example 2
[0052] The only difference from Example 1 is that the amount of material of agent A in Example 1 is adjusted, and the amount of MgO added is 3.42g, 3.99g, 4.56g, 5.13g, and 5.70g (corresponding to Figure 1 The MgO ratio of the horizontal axis is: 1.5, 1.75, 2.0, 2.25, 2.5), and the amount of MgCl2 added is 1.596g, 1.938g, 2.280g, 2.622g, 2.964g (corresponding to Figure 1 25 groups of orthogonal experiments were conducted, and the experimental results are shown in Figure 1 It can be seen that when MgO is 4.56g and MgCl2 is 2.28g, the briquette product has the highest drop strength.
[0053] Example 3
[0054] The only difference from Example 1 is that the proportion of the B agent component in the example is adjusted, and the amount of CaO added is 2.64g, 3.08g, 3.52g, 3.96g, and 4.40g (corresponding to Figure 2The CaO ratio on the horizontal axis is 1.5, 1.75, 2.0, 2.25, 2.5), and the KH2PO4 addition amount is 7.008g, 7.884g, 8.760g, 9.636g, 10.512g (corresponding to Figure 2 4KH2PO4, 4.5KH2PO4, 5KH2PO4, 5.5KH2PO4, 6KH2PO4 in the figure), 25 groups of orthogonal experiments were carried out, and the experimental results are shown in Figure 2 It can be seen that when CaO is 3.52g and KH2PO4 is 8.76g, the briquette product has the highest drop strength.
[0055] Example 4
[0056] The ratio of agent A to agent B in the embodiment was adjusted, and the mass of MgO and MgCl2 in agent A was 3.648g and 1.824g; 4.560g and 2.280g; 5.472g and 2.736g (corresponding to Figure 3 The horizontal axis of component A: 0.8, 1.0, 1.2), and the addition amounts of CaO and KH2PO4 in agent B are 2.816g, 7.008; 3.520g, 8.760g; 4.224g, 10.512g (corresponding to Figure 3 0.8 component B, 1.0 component B, 1.2 component B) in the figure, 9 groups of orthogonal experiments were carried out, and the experimental results are shown in Figure 3 It can be seen that when the A agent contains 3.52g of MgO, 2.28g of MgCl2, 3.52g of CaO and 8.76g of KH2PO4, the finished briquette has the highest drop strength.
Claims
1. A dust ash briquetting binder, characterized in that: In parts by mass, it includes 0.8 to 1.2 parts of agent A, 1.5 to 2.1 parts of agent B, and 2.1 to 2.9 parts of a molding agent; wherein the agent A includes MgO and MgCl2; the agent B includes CaO and a buffer; and the molding agent includes montmorillonite.
2. The dust ash briquetting binder according to claim 1, characterized in that: The mass ratio of MgO to MgCl2 is (1.5-2.5): (0.7-1.3); and / or, The mass ratio of the CaO to the buffer is (1.5-2.5):(4-6).
3. The dust ash briquetting binder according to claim 1, characterized in that: The montmorillonite is calcium-based montmorillonite, with a particle size satisfying that 90% of the particle size passes through an 800-mesh sieve, a pH value of ≥6.5, and a blue absorption amount of ≥42 g / 100 g; and / or, The buffer includes one or a combination of two or more of KH2PO4, acetic acid, and potassium acetate.
4. The dust ash briquetting binder according to claim 1, characterized in that: The MgO is calcined; Preferably, the calcination temperature is 1050-1350°C and the time is 3-6h; Preferably, the MgCl2 is dried; Preferably, the particle size of the agent A satisfies 90% passing through an 800-mesh sieve.
5. A dust ash briquette, characterized in that: The ash is mixed with the ash briquetting binder according to any one of claims 1 to 4 in a mass ratio of (75-92):(8-25), and then pressed to obtain the ash briquetting binder.
6. The dust ash briquette according to claim 5, characterized in that: The dust removal ash includes one or a combination of two or more of steelmaking coarse ash, steelmaking fine ash, steelmaking sludge, and iron oxide scale.
7. The dust ash briquette according to claim 6, characterized in that: The dust removal ash is composed of the steelmaking coarse ash, the steelmaking fine ash, the steelmaking sludge and the iron oxide scale in a mass ratio of (10-30):(30-60):(5-15):(15-35).
8. The dust ash briquette according to claim 5, characterized in that: The particle size of the dust removal ash is such that 90% passes through an 800-mesh sieve.
9. A method for preparing the dust briquette according to any one of claims 5 to 8, characterized in that: include: S1, mixing the agent A, the agent B, the molding agent, and water in a mass ratio of (0.8-1.2):(1.5-2.1):(2.1-2.9):(2.2-4.5), and stirring at 45-75° C. to obtain the dust ash briquetting binder; S2, mixing the dust removal ash and the dust removal ash briquetting binder, and performing a mixing process to obtain a slurry; S3, pressing the sludge, the pressing pressure is 5-15 MPa, and the pressing time is 15-30 minutes.
10. The preparation method according to claim 9, characterized in that: Within 1 hour before the pressing process, the S1 further comprises: The agent A is mixed with water at a mass ratio of 1:0.95-1.2 to obtain an A premix; the agent B is mixed with water at a mass ratio of 1:1.05-1.35 to obtain a B premix; the A premix and the B premix are stirred at 45-75° C. to obtain an A mixed solution and a B mixed solution respectively; Secondly, the A mixed solution, the B mixed solution, the molding agent and the water are mixed according to the ratio.